Frontispiz: Nanoporöse Filme mit regelmäßig angeordneten molekularen Motoren für lichtgesteuerte Adsorption und Diffusion. (9th January 2023) - Jiang, Yunzhe; Danowski, Wojciech; Feringa, Ben L.; Heinke, Lars
Abstract : Photochromic Materials . In their Communication (e202214202 ), Lars Heinke et al. report nanoporous films with oriented arrays of molecular motors for light‐controlled adsorption and diffusion.